Pengaruh Perputaran Persediaan, Perputaran Piutang Dan Rasio Lancar Terhadap Profitabilitas Pada PT. Kimia Farma Periode 2019-2022 - Syita Maghfirah; Dwi Saraswati (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2025)
This study aims to analyze the effect of inventory turnover, accounts receivable turnover, and current ratio on profitability at PT Kimia Farma, Tbk during the 2019-2022 period. Profitability is measured using Return on Assets (ROA) as the main indicator. The data used comes from the company's quarterly financial statements with a total of 18 observations. The analysis method includes descriptive statistics, classical assumption test, multiple linear regression, and model feasibility test using SPSS version 25. The results showed that inventory turnover, accounts receivable turnover, and current ratio have a significant effect on profitability, both partially and simultaneously. Efficient inventory turnover and receivables increase cash flow, while a stable current ratio reflects the company's ability to meet its short-term obligations. The Adjusted R² value of 79.5% indicates that these variables are able to explain profitability significantly. This study confirms the importance of optimal financial management to increase company profitability. Strategies that focus on operational efficiency, inventory management, and receivables can help PT Kimia Farma maintain competitiveness in a competitive market.